Histamine levels in plasma, blood, and urine in severe asthma, and the effect of corticosteroid treatment. Issue 6 (December 1976) - Bruce, C; Weatherstone, R; Seaton, A; Taylor, W H
Abstract : Plasma, whole blood, and urinary histamine levels have been determined in 64 normal subjects, in 10 patients with severe asthma, and in 10 control patients with other illnesses. The mean whole blood levels did not differ between the three groups. The mean plasma level in the asthmatics was significantly greater than that of the normal subjects but not of the control patients. The urinary histamine output was lower in the control patients than in the normal subjects but in the asthmatics did not differ from that of the normals. Corticosteroid therapy caused a marked fall, often to barely detectable levels, of the whole blood histamine concentration of the asthmatic patients and restored the plasma levels to normal but did not affect urinary histamine levels.